Effect of Ginger Extracts and Storage Temperature on Shelf Life of Kent Mango Fruits - Adams, Abdul-Rahaman; Salifu, Abdul Wahab; Chonga, John; Thomas , Bayuo (Journal of Postharvest Technology, 2016)
Postharvest loss is a major problem affecting fresh mango trade in most developed  and developing nations. The ability of mango farmers, distributors, processors and  consumers to use natural plants extracts and solutions to maintain fruits quality will  significantly affect quality and return on investments. This research was conducted  to discover the effects of immersion tomato fruits in dissolved ginger extracts on  Total Soluble Solid, Weight loss, pH, Flesh firmness, Pulp cube texture and  Consumer acceptance of Kent mango fruits stored at 5°C and 25°C for 12 days. One  hundred and twenty eight (128) Kent mango fruits were used for the experiment.  The entire sample was divided into four and each division was replicated two times.  The research confirmed that the treatment that reduced weight loss better was shown  by Twenty minutes solution for 5°C with 4.5%. Also, immersing of mango fruits in  dissolved ginger extract for 30 minutes at 25°C was appropriate in TSS and pH  which resulted in better taste. In respect of the flesh firmness a short immersing  duration at 5°C was found with the best sweet taste keeping the flesh firmness  better. In all the cases immersing of fruits sample in dissolved ginger extract resulted  in better quality than non-treated samples. Therefore , based on the results produced  it can safely be concluded that immersing of Kent mango fruits in dissolved ginger  extract offered a promise for adoption for small scale postharvest management of  Kent mango fruits.
Keywords: Kent mango; Postharvest quality Storage life; Plant extract; Shelf life